Modulation and Visualization of EF‐G Power Stroke During Ribosomal Translocation. (20th September 2019) - Yin, Heng; Gavriliuc, Miriam; Lin, Ran; Xu, Shoujun; Wang, Yuhong
Abstract: During ribosome translocation, the elongation factor EF‐G undergoes large conformational change while maintaining its contact with the moving tRNA. We previously measured a power stroke accompanying EF‐G catalysis, which was consistent with structural studies. However, the role of power stroke in translocation fidelity remains unclear. Here, we report quantitative measurements of the power strokes of structurally modified EF‐Gs by using two different techniques and reveal the correlation between power stroke and translocation efficiency and fidelity. We discovered that the reduced power stroke only lowered the percentage of translocation but did not introduce translocation error. The established force ‐structure–function correlation for EF‐G indicates that power stroke drives ribosomal translocation, but the mRNA reading frame is probably maintained by ribosome itself. Furthermore, the microscope detection method reported here can be simply implemented for other biochemical applications. Abstract : Power stroke : The ribosome translocase EF‐G generates substantial power stroke during translocation when its conformational change is not restricted. A short crosslinker restricting the conformational change will reduce this force by nearly 30 pN. The reduced power stroke decreases the translocation efficiency but does not introduce translocation error.